2021
DOI: 10.3390/antibiotics10111421
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Concentrations of Meropenem and Vancomycin in Ventriculitis Patients Obtained by TDM-Guided Continuous Infusion

Abstract: Effective antibiotic therapy of cerebral infections such as meningitis or ventriculitis is hindered by low penetration into the cerebrospinal fluid (CSF). Because continuous infusion of meropenem and vancomycin and routine therapeutic drug monitoring (TDM) have been proposed to optimize antimicrobial exposure in ventriculitis patients, an individualized dosing strategy was implemented in our department. We present a retrospective analysis of meropenem and vancomycin concentrations in serum and CSF in the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Most studies described the management of individuals with CNS infections using CSF and/or blood TDM of vancomycin, 16 , 18–29 often alongside TDM of other co-administered antibiotics including meropenem, 16 , 18 , 27 , 29 piperacillin/tazobactam, 26 gentamicin, 21 levofloxacin 26 and ciprofloxacin. 26 Other studies described CSF and/or blood TDM of linezolid, 17 , 30 flucloxacillin, 31 colistin 32 and ceftazidime/avibactam.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies described the management of individuals with CNS infections using CSF and/or blood TDM of vancomycin, 16 , 18–29 often alongside TDM of other co-administered antibiotics including meropenem, 16 , 18 , 27 , 29 piperacillin/tazobactam, 26 gentamicin, 21 levofloxacin 26 and ciprofloxacin. 26 Other studies described CSF and/or blood TDM of linezolid, 17 , 30 flucloxacillin, 31 colistin 32 and ceftazidime/avibactam.…”
Section: Resultsmentioning
confidence: 99%
“…They compared the ratio of CSF concentration to serum trough concentration on the day 3 or 4 with 500 mg intravenously every 6 h, and they showed that CSF/serum ratio was 0.291 ± 0.118. Tiede et al (16) reported the vancomycin CSF/serum ratio was only 7% in nine patients with ventriculitis secondary to subarachnoid hemorrhage. They compared the drug concentration in blood and CSF at 24 and 72 h after the start of continuous intravenously infusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ongoing large multicenter BLING trial program has demonstrated the feasibility of continuous meropenem infusion (29)(30)(31). Tiede et al used continuous meropenem and vancomycin infusion with therapeutic drug monitoring-guided dose optimization for successful treatment of ventriculitis in a retrospective cohort study (32). Continuous infusion may have varying impacts upon CSF penetration.…”
Section: Discussionmentioning
confidence: 99%